Management Education and Training at the Research and Development Agency for Legal and Judicial Education and Training at the Supreme Court of the Republic of Indonesia - Muhamad Yusup; Achmad Sanusi; Sutaryat Trinamansyah; Tb. Abin Syamsudin (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2021)
This research is a descriptive qualitative study aimed at describing the practice of management education and training at the Research and Development Agency for Legal and Judicial Education and Training at the Supreme Court of the Republic of Indonesia. In this research, data was collected through interview, observation and documentation techniques. The data that has been collected is then analyzed using data analysis techniques, the Miles and Huberman model, which consists of data reduction, data presentation, and drawing conclusions. Based on the research results obtained six findings. First, education and training activities are based on KMA Number 140 / KMA / SK / K / 2008. Second, the governance of the education and training program of the Education and Training Research and Development Agency for Law and Justice of the Supreme Court of the Republic of Indonesia consists of planning, implementing, and evaluating activities. Third, there are two strategies implemented in the implementation of education and training at the Supreme Court of the Republic of Indonesia, namely strategies in learning and strategies in developing education and training programs. Fourth, based on the research results, it can be seen that there are problems and weaknesses in the components in the implementation of education and training, such as participants, teaching staff, and facilities and infrastructure. Fifth, there are changes that are being made to make improvements, such as improving the use of technology and increasing the budget for the implementation of education and training. Sixth, there are two anticipatory steps taken towards the governance of the implementation of education and training to obtain optimal results.